2019
DOI: 10.1007/s10853-019-04230-z
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and physico-chemical properties of poly(N-vinyl pyrrolidone)-based hydrogels with titania nanoparticles

Abstract: Poly(N-vinyl pyrrolidone) (PVP)-based hydrogels with titania nanoparticles (TN) were synthesized by the sol-gel method for the first time and were characterized in different states (native, freeze-dried, air-dried to constant weight and ground to powder, or swollen to constant weight in H 2 O or D 2 O) by various methods such as wide-angle and small-angle X-ray and neutron scattering, neutron spin-echo (NSE) spectroscopy, and scanning electron microscopy. The static (static polymer-polymer correlation length (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 45 publications
0
22
0
Order By: Relevance
“…Several characteristics, such as properties and applications, especially biomedical applications, of a hydrogel depend on the pore size of the inner structure, dispersion of NPs, and morphology [ 22 , 23 ]. For instance, the adsorption ability of a hydrogel is determined by the pore size, and the size of the drug determines whether the drug can be entrapped in the hydrogel network [ 24 , 25 ]. Scanning electron microscopy results indicated that the PEG-DA/PDA/PUE/FA hydrogel was highly interconnected and infiltrated throughout the pores.…”
Section: Resultsmentioning
confidence: 99%
“…Several characteristics, such as properties and applications, especially biomedical applications, of a hydrogel depend on the pore size of the inner structure, dispersion of NPs, and morphology [ 22 , 23 ]. For instance, the adsorption ability of a hydrogel is determined by the pore size, and the size of the drug determines whether the drug can be entrapped in the hydrogel network [ 24 , 25 ]. Scanning electron microscopy results indicated that the PEG-DA/PDA/PUE/FA hydrogel was highly interconnected and infiltrated throughout the pores.…”
Section: Resultsmentioning
confidence: 99%
“…The produced PPRs can precipitate through hydrogen bonding interactions between the external hydroxyl groups of the threaded α‐CD molecules 39 . Additionally, the diffractogram of PEG200/α‐CD64 shows a broad amorphous halo centered at 28° (d = 0.32 nm) corresponding to the short‐range local order of free water clusters occluded into the nanopores of the hydrogel, bound water (OH··· H  O  H ···OH linking via hydrogen bonds in PPR hydrogels) and half‐bound water (water molecules attached to hydrophilic zones in the PPR) 40 . This diffuse halo also has the contribution of the amorphous domains of PEG chains, which allow the retention of water into the PPR hydrogels 41 .…”
Section: Resultsmentioning
confidence: 99%
“…Several characteristics, such as properties and applications, especially biomedical applications, of a hydrogel depend on the pore size of the inner structure, dispersion of NPs, and morphology [27][28] . For instance, the adsorption ability of a hydrogel is determined by the pore size, and the size of the drug determines whether the drug can be entrapped in the hydrogel network [29][30] . Scanning electron microscopy results indicated that the PEG-DA/PDA/PUE/FA hydrogel was highly interconnected and in ltrated throughout the pores.…”
Section: Resultsmentioning
confidence: 99%